Vagal tone as a biomarker of long‐term memory for a stressful social event at 4 months. Issue 7 (29th August 2014) - Montirosso, Rosario; Provenzi, Livio; Tronick, Ed; Morandi, Francesco; Reni, Gianluigi; Borgatti, Renato
ABSTRACT This study investigates infants' memory for social stress after a 15‐day retention interval using behavior and respiratory sinus arrhythmia (RSA). Experimental group infants were exposed to face‐to‐face still‐face paradigm (FFSF) two times; the first time at 4 months and after a 2‐week interval. Control group infants were exposed to FFSF only once at 4 months plus 2 weeks. Infants were categorized as suppressors or non‐suppressors based on the direction of RSA change at first FFSF exposure. No behavioral differences were found among groups and exposure conditions. In the experimental group suppressors changed and showed no suppression when re‐exposed 2 weeks later to FFSF. Non‐suppressors showed no change in RSA from the first to the second exposure to FFSF. Control infants showed similar RSA changes to experimental infants at their first exposure. Findings indicate that 4‐month‐old infants have memory for social stress related to individual differences in autonomic reactivity. © 2014 Wiley Periodicals, Inc. Dev Psychobiol 56: 1564–1574, 2014.